Past due - Lashner, William (New York : HarperTorch, 2004)
When Joey Cheaps is murdered less than twenty-four hours after telling Victor Carl a twenty-year-old secret, Victor decides to investigate, but soon finds his own life threatened.
National College of Business and Arts
Keywords: Impostors and imposture -- Fiction; Detective and mystery fiction